2022
DOI: 10.1182/blood.2021013233
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed NK-cell homeostasis associated with disease severity in chronic neutropenia

Abstract: Neutrophils have been suggested to play a critical role in terminal differentiation of NK cells. Whether this is a direct effect or a consequence of global immune changes with effects on NK cell homeostasis remains unknown. Here, we used high-resolution flow- and mass cytometry to examine NK cell repertoires in 64 patients with neutropenia and 27 healthy age- and gender-matched donors. A subgroup of patients with chronic neutropenia showed severely disrupted NK cell homeostasis manifested as increased frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…In mice lacking neutrophils due to mutations in Gfi-1 , NK cells hyperproliferate, yet they have poor survival, impaired function, and a block in maturation ( 52 ). Furthermore, some individuals with congenital neutropenia have a decreased frequency of CD56 dim NK cells in the periphery and NK cell functional impairment ( 52 , 53 ), a phenotype very similar to that seen in MCM- and GINS-deficient individuals. In the proband (II.1) described in our study, as in GINS1 deficiency, neutropenia was corrected by treatment with G-CSF.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In mice lacking neutrophils due to mutations in Gfi-1 , NK cells hyperproliferate, yet they have poor survival, impaired function, and a block in maturation ( 52 ). Furthermore, some individuals with congenital neutropenia have a decreased frequency of CD56 dim NK cells in the periphery and NK cell functional impairment ( 52 , 53 ), a phenotype very similar to that seen in MCM- and GINS-deficient individuals. In the proband (II.1) described in our study, as in GINS1 deficiency, neutropenia was corrected by treatment with G-CSF.…”
Section: Discussionmentioning
confidence: 89%
“…In other words, perhaps the neutrophil deficiency is extrinsic and secondary to the deficiency of NK cells. Alternatively, there may be a unique requirement associated with immune cell proliferation and apoptosis that is common to NK cells and neutrophils ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In NK cells, 54 upregulated and 7 downregulated genes were identified in HCC, most of which had been reported to be involved in the p53 signaling pathway and cell cycles, such as CCNB1, CCNB2, CDK1, PTTG1, PLK1, MAD2L1, GTSE1, and TOP2A. These genes and related pathways were demonstrated to maintain NK cell homeostasis ( 24 ). Moreover, some other DEGs, including HSPA1A, HSPA1B, HSPA5, HSPA6, IFNG, CD8B, and KIR2DL3, were reported to participate in antigen processing and presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, according to our results, the allogeneic NK-mediated GVL effects were transient after engraftment in the murine MHC class I mismatched HSCT setting. Recently, the effect of NK regulated by neutrophils in human has been reported which found that patients with chronic neutropenia displayed a specific gap in the NK repertoire, associated with poor cytotoxic function and more severe disease manifestations [ 36 ]. The GVL effects of NK cells were transient due to a problem at the functional maturation of NK cell after HSCT; thus, appropriate stimulation for NK cell licensing by enriched neutrophils should be needed.…”
Section: Discussionmentioning
confidence: 99%